Recent Advances in Mitochondrial Fission/Fusion-Targeted Therapy in Doxorubicin-Induced Cardiotoxicity - Chayodom Maneechote; Siriporn C. Chattipakorn; Nipon Chattipakorn (MDPI AG, 2023)
Doxorubicin (DOX) has been recognized as one of the most effective chemotherapies and extensively used in the clinical settings of human cancer. However, DOX-mediated cardiotoxicity is known to compromise the clinical effectiveness of chemotherapy, resulting in cardiomyopathy and heart failure. Recently, accumulation of dysfunctional mitochondria via alteration of the mitochondrial fission/fusion dynamic processes has been identified as a potential mechanism underlying DOX cardiotoxicity. DOX-induced excessive fission in conjunction with impaired fusion could severely promote mitochondrial fragmentation and cardiomyocyte death, while modulation of mitochondrial dynamic proteins using either fission inhibitors (e.g., Mdivi-1) or fusion promoters (e.g., M1) can provide cardioprotection against DOX-induced cardiotoxicity. In this review, we focus particularly on the roles of mitochondrial dynamic pathways and the current advanced therapies in mitochondrial dynamics-targeted anti-cardiotoxicity of DOX. This review summarizes all the novel insights into the development of anti-cardiotoxic effects of DOX via the targeting of mitochondrial dynamic pathways, thereby encouraging and guiding future clinical investigations to focus on the potential application of mitochondrial dynamic modulators in the setting of DOX-induced cardiotoxicity.